Pengaruh Pemberian Giberelin terhadap Pertumbuhan dan Produksi Empat Varietas Kedelai (Glycine max L. Merrill) - Sudirman, Sudirman; Rasyad, Aslim; Nurhidayah, Tengku (Jurnal Agro Teknologi Tropika, 2015)
Growth regulators such as gibberellic acid (GA3) is expected to remove and prevent barriers imposed by geneticand enviromnental effect on plant growth and supposed to increase crop production. In this study, we intended todetermine the effect of GA3 on agronomic and yield components of four soybean varieties. The field experiment wasarranged in a split plot design with three replications. Three levels of GA3 concentrations such as 0 ppm as control, 125ppm and 250 ppm were assigned as main plot and sprayed over the plant at 21 days after planting. Four varietiesincluding Kaba, Grobogan, Wilis and Anjasmoro were used as subplots and the seed of each variety was sown in a plotsize of 3,2 m x 3 m. Several growth parameters and yield components were observed from each plot. The results showedthat GA3 effect was inconsistent for the four varieties. It appeared from this study that GA3 did not affect leaf area index,time to flower, time to harvest, number of filled pods per plant, seed number per plant, and harvest index for all varieties.Application of GA3 at levels of 125 and 250 ppm increased crop growth rate, plant height and internode length of mainstem in all genotypes except Anjasmoro. The main impact of different levels of GA 3 application was an increase in seedweight per plant and grain yield. The highest grain yield was achieved with application of 125 ppm GA 3 for Kaba andGrobogan and of 250 ppm for Wilis and Anjasmoro. This imply that application of GA 3 to soybeans genotypes has to betaken care with cautiously according to the genotypes.